A companion to Mexican history and culture - Beezley, William H. (Chichester, West Sussex : Wiley-Blackwell, 2011)
'A Companion to Mexican History and Culture features 40 essays contributed by international scholars that incorporate ethnic, gender, environmental, and cultural studies to reveal a richer portrait of the Mexican experience, from the earliest peoples to the present. Features the latest scholarship on Mexican history and culture by an array of international scholars Essays are separated into sections on the four major chronological eras Discusses recent historical interpretations with critical historiographical sources, and is enriched by cultural analysis, ethnic and gender studies, and visual evidence The first volume to incorporate a discussion of popular music in political analysis'--
'A Companion to Mexican History and Culture features 40 carefully chosen essays that focus on new approaches to the rich tradition of Mexican history. Essays by a variety of international scholars serve to broaden accounts of the Mexican experience through the incorporation of ethnic, gender, environmental, and cultural studies. An introductory section providing overall context is followed by essays focusing on the major chronological eras in Mexican history: Indigenous Cultures before Columbus, Colonial New Spain, and Independent Mexico, which is divided into two sections. Principal historic figures, institutions, the environment, and scientific and medical developments are discussed in individual essays. Also covered are recent historical interpretations with critical historiographical sources. The readings in A Companion to Mexican History and Culture reflect the important new trends in the study of history that have led to a more sensitive narrative and revealing portrait of Mexico's dramatic and complex past and rich cultural traditions'--
Includes bibliographical references and index.
Keywords: HISTORY / Latin America / General; Mexico -- History; Mexico -- Civilization